2010
DOI: 10.1111/j.1600-6143.2009.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1/B7‐H1 Interaction Contribute to the Spontaneous Acceptance of Mouse Liver Allograft

Abstract: †Miwa Morita and Masayuki Fujino contributed equally to this work.The programmed death-1 (PD-1)/B7-H1 pathway acts as an important negative regulator of immune responses. We herein investigated the role of the PD-1/B7-H1 pathway in establishing an immunological spontaneous tolerance status in mouse liver allografting. B7-H1 is highly expressed on the donor-derived tissue cells and it is also associated with the apoptosis of infiltrating T cells in the allografts. Strikingly, a blockade of the PD-1/B7-H1 pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 19 publications
7
100
0
Order By: Relevance
“…Nonhematopoietic PDL1 expression has been reported to be of key importance in murine autoimmune diabetes, in which pancreatic islet cells lacking PDL1 led to earlier onset diabetes associated with significant CD4 + T-cell infiltration and activation (4) and endothelial PDL1 expression was shown to protect the myocardium against T-lymphocyte-induced myocarditis (13). Furthermore, PDL1 expression on sinusoidal endothelial cells and Kupffer cells are known to be essential for liver transplant spontaneous tolerance (14). Our studies show for the first time that PDL1 expression by the endothelium is required to achieve cardiac allograft tolerance in a fully allogeneic mismatched model.…”
Section: Pdl1 Of Donor Endothelium In Allograft Tolerance Similar Surmentioning
confidence: 99%
“…Nonhematopoietic PDL1 expression has been reported to be of key importance in murine autoimmune diabetes, in which pancreatic islet cells lacking PDL1 led to earlier onset diabetes associated with significant CD4 + T-cell infiltration and activation (4) and endothelial PDL1 expression was shown to protect the myocardium against T-lymphocyte-induced myocarditis (13). Furthermore, PDL1 expression on sinusoidal endothelial cells and Kupffer cells are known to be essential for liver transplant spontaneous tolerance (14). Our studies show for the first time that PDL1 expression by the endothelium is required to achieve cardiac allograft tolerance in a fully allogeneic mismatched model.…”
Section: Pdl1 Of Donor Endothelium In Allograft Tolerance Similar Surmentioning
confidence: 99%
“…The fold change vs one sample of the control group was calculated as described previously. 13 Oxidative Damage Measurement The oxidative stress marker 8-hydroxydeoxyguanosine was measured with an enzyme-linked immunosorbent assay kit (Japan Institute for the Control of Aging, Shizuoka, Japan), according to the manufacturer's instructions. 8-OHdG, a product of oxidatively damaged DNA, was detected using a competitive enzyme-linked immunosorbent assay using a monoclonal antibody (clone N45.1) that is specific for DNA damage.…”
Section: Rna Isolation and Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…However, various experimental animal studies showed enhanced rejection and/or decreased graft survival after blockade of coinhibitory receptors in organ-transplanted mice. This implies that coinhibitory receptors are involved in suppressing allograft rejection in mice (23)(24)(25)(26). However, the role of T cell exhaustion and coinhibitory receptor-ligand interactions in human solid organ transplantation have not been widely studied (25).…”
mentioning
confidence: 99%